(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
Owing to evolve the technological and scientific requirements, reliability plays an essential part in mathematical and Statistical disciplines. The method of independent trials has been the focus of most contemporary probability assessments. These operations are the cornerstone of classical probability and a large part of statistics. The “Law of Large Numbers” and the “Central Limit Theorem” were two of the primary theorems for such processes that were studied. We demonstrated that the general outcome occurs when a series of chance tests create an independent testing procedure.